PENGARUH MOL REBUNG BAMBU TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY - Abdullah Samosir; Gusniwati . (Bioplantae, 2014)
This study aimed to determine the effect of local microorganisms from fermented bamboo shoots (LM) on the growth of oil palm seedlings in pre nursery. This research used completely randomized design consisting of 6 levels of treatment: Urea 2.0 g / L of water, 50.0 ml , 100.0, 150.0, 200.0 and 250.0 ml of LM from fermented bamboo shoots. The growth parameter plant height, leaf area, root dry weight, and shoot dry weight was measured every week. The results showed LM from bamboo shoots fermented significantly affected oil palm seedling growth at 50 ml /L of water. The highest in seedling height, diameter of seedling, number of leaves, leaf area, dry weight, root dry weight was achieved at 50.0 ml/L water of LM. Keywords: Bamboos, local microorganism, fermented, pre-nursery